Raiva em equino no município de Porto Alegre - RS, Brasil - Merini, Luciana Paula; Cormelato, Alexandra Tirso; Beck, Carlos Afonso de Castro; Garbade, Petra; Bueno, Flávia Umpierre; Pedroso, Pedro Miguel Ocampos; Carnesella, Samuel (Acta Scientiae Veterinariae, 2018)
Background : : : : rabies is a fatal zoonosis caused by a highly neurotropic RNA virus which causes neurological signs and that is distributed almost worldwide. Rabies affects domestic and wild animals and this is a disease transmitted by their bites, through which the virus present in the saliva is inoculated. In Brazil, Desmodus rotundus is the main hematophagous bat species that transmits rabies, especially to herbivores e equines. In equines, the clinical manifestation varies a lot, including both the paralytic and the furious form of the disease. The goal of this study is to describe a case of equine rabies in the city of Porto Alegre, Rio Grande do Sul, Brazil. Case: a six-year old male American Quarter Horse, which presented a clinical picture characterized by colic, depraved appetite and difficulty to move, was admitted to the Hospital de Clínicas Veterinárias of Universidade Federal do Rio Grande do Sul (HCV-UFRGS). The horse did not respond to treatment, therefore, it was submitted to exploratory laparotomy, when the moderate intestinal constipation and low intestinal motility was observed. A large colon enterotomy was performed and the intestinal contents were partially emptied. During recovery from anesthesia, the animal remained in lateral decubitus, not making any attempt to stand up. The animal did not show a favorable clinical evolution a few hours later, displaying weakness particularly in the hind limbs. Consequently, the animal underwent euthanasia. Samples of body organs were collected and fixed in formol 10%, processed routinely for histological purposes and then stained by hematoxylin and eosin. The histopathological examination revealed nonsuppurative meningoencephalitis in the central nervous system, without the presence of Negri bodies. Due to the history of recent rabies cases in neighbor areas of the property from where the animal came, direct immunofluorescence (IFD) and immunohistochemical (IHQ) exams for rabies were requested. The result was negative in IFD and a positive immunolabeling was observed in IHQ, thus demonstrating a viral antigen labeling in neurons of the cervical spine, pons, mesencephalon and cerebellum. Discussion: intracytoplasmic inclusions, also known as Negri bodies, are important and pathognomonic findings that were not observed in this case. Its presence and concentration depend on the stage and course of the disease, and they are not present in up to 30% of rabies cases, because certain virus strains do not produce Negri bodies. In equines, the occurrence of Negri bodies is less frequent than in bovines. IFD is the most adequate rabies diagnosis method, which is a highly sensitive technique (80-100%). The result was negative for this case, being confirmed only by IHQ. The immunohistochemical test is an important laboratorial diagnosis tool of rabies, because it allows the solution of unspecific meningoencephalitis cases when Negri bodies are not present. The treatment of animals with rabies is not considered. Vaccination in endemic regions or in areas where a rabies case has occurred is necessary. Rabies cases near the property where the animal lived were reported, but a prophylactic vaccination was not carried out. Rio Grande do Sul had a peculiar epidemiological status regarding rabies, as urban rabies cases had not been reported for approximately 17 years. However, rabies transmitted by hematophagous bats is still endemic in rural areas. This case demonstrates the importance of maintaining a rabies vaccination schedule in equine properties.